'[P]Lainer, If Possible, than Ever': Plainness and Self-Representation in Charlotte Brontë's 'Henry Hastings'. (2nd October 2022) - AlBassam, Mona
Abstract: Charlotte Brontë's juvenilia, unlike her mature novels with their independent plain heroines, is dominated by female beauties who represent her imaginary aristocratic world. The desire for beauty that dominated Brontë's early writings is abandoned in the tale 'Henry Hastings' (1839) and the heroine's plainness comes to create a substitute for the image of female beauty. In considering Elizabeth Hasting's plainness as a form of self-representation, this article challenges the perception of plainness as merely an indication of the heroine's invisibility or more profoundly a reflection her interiority and morality. Instead, this paper explores the exteriority and subversiveness of Elizabeth's plainness in the narrative. Plainness in 'Henry Hastings' is not only related to homeliness but also goes into the realm of plainness as a self-imposition, particularly through dress. The heroine's beauty or on the other hand, her plainness, as I will argue, comes to offer different positions of making the self visible to the dominant male gaze in the late juvenilia.